2014
DOI: 10.1186/1476-4598-13-65
|View full text |Cite|
|
Sign up to set email alerts
|

Alpha-enolase as a potential cancer prognostic marker promotes cell growth, migration, and invasion in glioma

Abstract: BackgroundThe success of using glycolytic inhibitors for cancer treatment relies on better understanding the roles of each frequently deregulated glycolytic genes in cancer. This report analyzed the involvement of a key glycolytic enzyme, alpha-enolase (ENO1), in tumor progression and prognosis of human glioma.MethodsENO1 expression levels were examined in glioma tissues and normal brain (NB) tissues. The molecular mechanisms of ENO1 expression and its effects on cell growth, migration and invasion were also e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

14
171
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 179 publications
(194 citation statements)
references
References 47 publications
(40 reference statements)
14
171
0
Order By: Relevance
“…4A). It has been reported that ENO1 can control the expression of cell cycle associated genes via PI3K/AKT pathway in glioma [12]. Therefore, we evaluated the expression of Cyclin D1 and Cyclin E in OCI-Ly8 and Daudi cells.…”
Section: Eno1 Regulated Cell Cycle Associated Gene and Pi3k/akt Signamentioning
confidence: 99%
See 1 more Smart Citation
“…4A). It has been reported that ENO1 can control the expression of cell cycle associated genes via PI3K/AKT pathway in glioma [12]. Therefore, we evaluated the expression of Cyclin D1 and Cyclin E in OCI-Ly8 and Daudi cells.…”
Section: Eno1 Regulated Cell Cycle Associated Gene and Pi3k/akt Signamentioning
confidence: 99%
“…Overexpression of ENO1 is associated with glioma progression. Knockdown of ENO1 expression led to suppressed cell growth, migration and invasion progression by inactivating the PI3K/AKT pathway in glioma cells [12].…”
Section: Introductionmentioning
confidence: 99%
“…63 It is shown that the knockdown of ENO1 expression led to suppressed cell growth and migration by inactivating the PI3K/Akt pathway in glioma cells. 63 Tear proteomic analysis of patients with type 2 diabetes with dry eye syndrome shows alteration in expression of ENO1 65 as well as results on DR in rat. 25 Another hub-bottleneck after laser therapy is ALDOA, which can be suggested as a common hub-bottleneck for DR progression and laser therapy.…”
Section: Discussionmentioning
confidence: 99%
“…Its overexpression has been associated with multiple tumors. [62][63][64] In many of these tumors, ENO1 promoted tumorgenesis via activating and regulating the PI3K/ AKT signaling pathway. 63 It is shown that the knockdown of ENO1 expression led to suppressed cell growth and migration by inactivating the PI3K/Akt pathway in glioma cells.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation